Connecting two phenazines with a four-membered ring: the synthesis, properties and applications of cyclobuta[1, 2-b:3, 4-b′]diphenazines12. Issue 14 (25th October 2017) - Yang, Shuaijun; Chu, Ming; Miao, Qian
Abstract : This study puts forth a new π-electron molecular scaffold containing two phenazine moieties connected by a four-membered ring. It exhibits interesting optical and electronic properties and sheds light on the role of the four-membered ring in conjugation. Abstract : Herein we report cyclobuta[1, 2- b :3, 4- b ′]diphenazine (CBDP), a new π-electron molecular scaffold containing two phenazine moieties connected by a four-membered ring. With properly positioned silylethynyl substituting groups, CBDP offers a chromophore with a large molar extinction coefficient, a luminophore with a good quantum yield, and an n-type organic semiconductor with a field effect mobility as high as 0.30 cm 2 V −1 s −1 . These properties are not available in the phenazine reference compounds, but can be tuned by adjusting the substitution positions of the silylethynyl groups. On the basis of single crystal structures, UV-vis absorption and DFT calculations, it is concluded that the two phenazine subunits in CBDP are poorly conjugated in the ground state but strongly conjugated in the excited state, shedding light on the role of the four-membered ring in conjugation.